Effectiveness of Role-Playing Method in Improving Elementary School Children's Knowledge about DHF Prevention in South Balikpapan - Zidni Ilman Nafi'a; Siti Arifah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Dengue fever (DHF) is a major public health problem in the tropics, including Indonesia, impacting the health of children. The disease can cause serious complications if not treated promptly. Effective prevention requires good knowledge of healthy behaviours, especially in environmental management to prevent the proliferation of Aedes aegypti as the main vector of the virus. However, many children still do not understand the importance of dengue prevention. Therefore, improving their knowledge is very important in an effort to overcome this problem. This study aims to analyse the effectiveness of interactive learning methods, particularly role-playing, in improving children's knowledge about dengue prevention. The research design used is Quasi-Experiment with pre-test and post-test, involving 27 students of SD Negeri 002 South Balikpapan in 2024. The instrument used was a questionnaire which was prepared based on the indicators of DHF prevention. The results showed a significant effect of interactive learning method on improving children's knowledge about dengue prevention, with a significance level of 0.000 (p < 0.05). This study provides important implications in health education, especially in efforts to improve children's knowledge through interactive and fun learning methods.